2024
DOI: 10.1002/bbb.2577
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the application of marine microalgae Dunaliella salina in a biorefinery context: production of value‐added biobased products

Fellipe César Cardoso de Souza Félix,
Vitor Bertolassi Hidalgo,
Ana Karine Furtado de Carvalho
et al.

Abstract: Microalgae are a rich source of bioactive compounds such as pigments, carbohydrates, lipids, proteins, and other substances of interest. Thus, given the possible variety of products that can be obtained from them, it is important to determine their biochemical composition, taking into consideration the species and cultivation conditions, so that they can be used as feedstock in biorefineries, with the aim of using all the biomass in the biorefining processes and increasing its economic viability. This work aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 56 publications
(113 reference statements)
0
0
0
Order By: Relevance
“…Previous studies had reported this boost in biomass production when the culture is subjected to high salinities [37]. The favorable biomass findings are particularly intriguing as microalgal biomass holds significant biotechnological promise for utilization in integrated multi-product biorefineries [38].…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies had reported this boost in biomass production when the culture is subjected to high salinities [37]. The favorable biomass findings are particularly intriguing as microalgal biomass holds significant biotechnological promise for utilization in integrated multi-product biorefineries [38].…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies had reported this boost in biomass production when the culture is subjected to high salinities [52]. The favorable biomass findings are particularly intriguing as microalgal biomass holds significant biotechnological promise for utilization in integrated multiproduct biorefineries [53]. Salt concentration and user error when washing the cells of salt may have affected results of Dry biomass assessment.…”
Section: Discussionmentioning
confidence: 99%